FINANCIAL MECHANISM FOR SUPPORTING ENTREPRENEURS AND HEDGING THEIR RISKS - R.K. Berstembaeva,; N.B. Rubenkova,; Zh.A. Toyzhigitova, (Academic Journal of Physical and Chemical Sciences, 2019)
The scientific article is devoted to such an important aspect as financial incentives for entrepreneurial activity and the search for new methods to stimulate it. At the moment, this issue has a wide meaning for both beginners and active entrepreneurs. The authors consider financial methods and forms of business stimulation, and also gives practical recommendations on their use. The purpose of entrepreneurship is to extract income through the production and supply to the market of goods, works or services, as well as to public recognition, awareness of its importance as an individual. However, the existing risks in the market of entrepreneurs are forced to take measures to reduce them. The company has the ability to reduce their own risk by attracting common problems to partners. In such cases, joint stock companies, financial and industrial groups can be created; enterprises can acquire shares or exchange them among themselves, enter into various consortia, associations, concerns.